Analisis Pengaruh Karakteristik Komite Audit Terhadap Financial Distress - Melisa Rahmawati; Marsono Marsono (Diponegoro Journal of Accounting, 2014)
The purpose of this research was to examine the impact of audit committee characteristics on financial distress.This research was replicated from the previous research, Rahmat et al., (2009). The difference between this research and the previous is in the sample and control variable. Previous study used listed companies in the Bursa Malaysia, while this research used only listed multinational manufacture companies in the Indonesia Stock Exchange in 2010-2012. In this research, control variable added is liquidity (based on the research of Fadhilah, 2013). The addition of these variable into research because these variable has influence on financial distress. This research is done to prove the influence of these variable on financial distress.. Population that use in this study is an entire company (non-banking) listed in Indonesia Stock Exchange in 2010-2012. Statistical data analysis method used is logistic regression. The hypotesis of this research is divided into five, size of audit committee, independence of audit committee member, frecuency of audit committee, number of fiancial literacy audit committee, and the hypothetical simultaneous effect on financial distress.The result of this research shows that size of audit committee and number of financial literacy audit committee have negatively significant influenced on financial distress. The frequency of audit committee and independence of audit committee member have no significant influence on financial distress. The control variable liquidity has negatively significant influenced on financial distress. The implications of this research indicate that size of audit committee and number of financial literacy audit committee have negatively impact to probability of financial distress. It is important to know the impact of audit committee characteristics on financial distress to minimize financial distress that occurred.